Assessing winter pasture quality in Sunnfjord wild reindeer area - Slåtsveen, Trine-Lise (UiT Norges arktiske universitet, 2019)
Winter pastures are bottlenecks for population trends for wild reindeer, and the quality and availability are important parameters when managing populations. Sunnfjord, considered on of the smallest wild reindeer districts in Norway, have never had a comprehensive evaluation of accessible winter pasture within. The aim of study is to assess the quality of winter forage in all tree sub- areas within Sunnfjord wild reindeer area. Result will be focused on field observations and supported by satellite remote sensing data. Field survey was carried out fall 2018 and spring 2019. The method in this study is developed by NINA and has previously been used in various part parts of Norway (i.e. Finnmark, Hardangervidda). Five sample sites was established along 12 transect lines and each sample site was comprised of five sample plots in a cross shaped grid. Lichen and winter forage biomass (g/m2) was later estimated using a formula Established by Gaare et al. (1999) and Wielgolaski (1975). A satellite remote sensed based approach was applied to map current lichen and green cover and to perform change detection over the whole range of Sunnfjord. For thus purpose a Sentinel-2 and Landsat 5 Thematic mapper ™ was used. Sunnfjord had and overall of 117 g/m2 in field plots, identical to heavy grazed areas in Finnmark and Hardangervidda. Still, it was better than expected considering costal areas in Norway have more suitable summer pastures and less suitable winter pastures. Winter forage biomass varied among areas, area 1 and 2 had the highest average g/m2, almost twice that of area 3. Height, and lichen cover was also highest in area 2. Satellite remote sensing results found no change in lichen and green cover between areas. Unlike previous studies, no interaction was found between field and satellite result, which could be a result of the method in use. During a 11year period from 2008-2019 an increase in green cover was observed. Lichen had decreased in area 1 and 2, while area 3 could be considered to have no change. No ...